Contribuição ao estudo fitoquímico de Cróton rhamnifolius (Euphorbiaceae) - Silva, Francisca Karen Souza da (2008)
The present work reports the study on the volatile chemical constitution of the leaves, twigs and roots of Croton rhamnifolius (Euphorbiaceae), popularly known in the Northeast of Brazil as “quebra-faca” (Port. Lit. = knife breaker) as well as of the non-volatile constituints of the roots. GC-MS analysis of the essential oil from leaves of C. rhamnifolius (OEFCR) allowed the identification of 21 constituents from which 1,8-cineol (31,81%) and - phelandrene (11,84%) were the major components. For the essential oil from twigs (OETCR) all 14 components were identified and - pinene (30,81%) and - cariophyllene (12,86%) were the major ones. For the essential oil from roots (OERCR) jsut 8 components were identified with valencene (25,97%) and borneol (20,05%) arising as the chief components. The phytochemical analysis of the ethanol extract from the roots led to the isolations and characterization of a diterpenoid incorporating an indol alkaloid moiety that hás been named as rhamnifolin (1), two beierene diterpenes, stachenone (2) and 12-oxostachenone (3), and two pentacyclic triterpenes: one, the 3-acetyl-olean-14-ene-28-oic acid (aleuritolic acid, AAA) (4) belonging to the oleanane and the other, lupeol (5), belonging to the lupane series. The structure determination of all non-volatile constituents was performed by mean of spectroscopic techniques such as MS, IR, 1H and 13C NMR, including uni and bidimensional pulse sequences. The identification of the volatile constitution was performed by GC-MS for the qualitative analysis while GC-FID was used for the quantitative analysis. Comparison to data published in the literature was also used for identification wherever the case.